Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.2172/890964
|View full text |Cite
|
Sign up to set email alerts
|

Seismological evidence for Lateral magma intrusion during the July 1978 deflation of the Krafla volcano in NE-Iceland

Abstract: The July 1978 deflation of the Krafla volcano in the volcanic rift zone of NE-Iceland was in most respects typical of the many deflation events that have occurred at Krafla since December 1975. Separated by periods of slow inflation, the deflation events are characterized by rapid subsidence in the caldera region, volcanic tremor and extensive rifting in the fault swarm that transsects the volcano. Earthquakes increase in the caldera region shortly after deflation starts and propagate along the fault swarm awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(198 citation statements)
references
References 2 publications
16
178
0
Order By: Relevance
“…We calculate the stress and strain due to a dyke segment opening in a similar manner and superpose them on the estimated tectonic contributions. Assuming a linear relationship between stress and strain, we then calculate the strain energy potential using equation (2). When inferring the path of preferred dyke propagation, we assume also that the dyke depth, with respect to sea level, is the same for all strikes tested.…”
Section: Authors Contributionsmentioning
confidence: 99%
“…We calculate the stress and strain due to a dyke segment opening in a similar manner and superpose them on the estimated tectonic contributions. Assuming a linear relationship between stress and strain, we then calculate the strain energy potential using equation (2). When inferring the path of preferred dyke propagation, we assume also that the dyke depth, with respect to sea level, is the same for all strikes tested.…”
Section: Authors Contributionsmentioning
confidence: 99%
“…In fact, it is well-known that, at the tip of an advancing dyke, tensile stresses can increase due to magma injection (Rubin and Pollard, 1988;Rubin, 1992) and exceed the Coulomb failure threshold, triggering earthquakes in the brittle crust (Brandsdóttir and Einarsson, 1979;Einarsson and Brandsdóttir, 1980;Feigl et al, 2000;Cattin et al, 2005). The effects of magmatic pressure at an advancing dyke have already been explored in several papers by field data, numerical modeling, and analog experiments (review in Rivalta et al, 2015, and reference therein).…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…Gaps in the distribution of seismicity associated with the intrusion of a magma dike have also been observed at Krafla [Einarsson and Brandsdottir, 1980] and Kilauea Volcanoes [Rubin and Gillard, 1998]. Rubin and Gillard [1998] concluded that dikes propagating into regions of low ambient differential stress are likely to produce no seismicity at the magnitude 1 level or above.…”
Section: Earthquake Swarm Descriptionmentioning
confidence: 99%